Analisis Faktor-Faktor yang Mempengaruhi Kredit Konsumsi pada Bank Persero di Indonesia - Faricha , Nur (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
This study aims to determine the effect of Third Party Funds, Inflation, Exchange Rates, and Capital Adequacy Ratio on consumer credit at Bank Persero in Indonesia. While this study uses secondary data. The analysis technique used is multiple linear regression with the results of the Independent variable test showing that Third Party Funds, inflation, and the Capital Adequacy Ratio have a positive and significant effect on consumer credit at Bank Persero in Indonesia. While the exchange rate has no significant effect on consumer credit at Bank Persero in Indonesia.